Scarcity-driven monetization of digital content - Kanuri, Vamsi K.; Pattabhiramaiah, Adithya (Frontiers in Research Metrics and Analytics, 2022)
In the last two decades, the U.S. news industry has undergone significant disruption, which resulted in nearly a 66% drop in overall revenues. Such a monumental decline in subscription and advertising revenues has led news publishers to experiment with new revenue generation strategies. Some of these strategies, such as instituting a paywall on the newspaper’s website and deploying a freemium business model, have gained in popularity due to their promise of generating additional subscription and advertising revenue. However, these strategies limit readers’ access to news, thereby contributing to news becoming a scarcer commodity. In contrast, alternative strategies such as reader-focused fundraising events aim to increase revenue organically by educating readers about the cost and value of quality journalism, with little implication for news scarcity. In this chapter, we survey several of these contemporary digital news monetization strategies with the goal of assessing the sustainability of scarcity-driven strategies. We offer conjectures about the conditions under which scarcity-driven strategies may be profitable relative to alternative monetization strategies and share some predictions about upcoming trends in the news industry.